Enhancing Energy Access in Rural Indonesia: A Holistic Assessment of a 1 kW Portable Power Generator Based on Proton-Exchange Membrane Fuel Cells (PEMFCs) - Handrea Bernando Tambunan; Reynolds Widhiyanurrochmansyach; Sabastian Pranindityo; Jayan Sentanuhady (Designs)
Hydrogen energy is a promising alternative to traditional fossil fuels, offering a clean and sustainable solution to address the challenges of climate change and environmental degradation. Fuel cells provide direct and environmentally friendly conversion of chemical energy from a fuel source into electrical energy, emitting only water vapor when utilizing hydrogen from renewable sources. This study delves into the design of a portable proton-exchange membrane fuel cell (PEMFC) device tailored for household use in rural areas. The research focuses on achieving a minimum peak power of 1000 W and a voltage of 220 VAC at 50 Hz for the fuel cell. Employing theoretical calculations derived from existing formulas and literature reviews, various fuel cell components are meticulously assessed, including real power, voltage drop, performance under current load, and pressure drop on the bipolar plate. Additionally, the study encompasses the selection of auxiliary components like converters, inverters, fans, and others. The resultant fuel cell design showcases a device capable of generating a peak power of 1132.32 W with an efficiency rating of 48.66%. Identifying suitable auxiliary components further contributes to developing a practical and efficient portable power solution for rural households.